Control system for noise-resistant electronic speed controller of a brushless electric motor for an unmanned aerial vehicle - M. V. Parinov; A. N. Yurov; Ya. V. Skitskiy (Российский технологический журнал)
Objectives. The high demand for unmanned aircraft and their efficiency makes the production of their components a matter of relevance. One of these components is the speed controller of the brushless electric motor of the propeller motor group. At the current time, Russian industry, however, does not mass-produce them. In order to start production, control methods and algorithms for the hardware and software parts of devices of this type are needed. Criteria for selecting the main components also need to be formalized. The aim of this work is to develop a method for the software control of electric motors. This includes block diagrams and invariant algorithms and methods for the calculated selection of parameters of the main microcontroller of the electronic speed controller.Methods. Methods of algorithmization, expert assessments, linear computational processes and experimental studies were used.Results. The paper presents the theoretical basis for controlling the required motors. It proposes a block diagram of the implementation of the controller, and a technique for switching windings when controlling with a trapezoidal signal is proposed. Examples are given in the form of an oscillogram. Based on theoretical research, an invariant algorithmic apparatus was developed for building software for various types of microcontrollers. Block diagrams of all the main modules of the software are also presented. The main ones include: the event switching algorithm; and the main endless loop of the microcontroller. The requirements for microcontrollers to create the various types of speed controllers are formalized herein and presented in the form of a set of mathematical expressions. They enable the number of required peripheral devices and microcontroller ports to be calculated according to the requirements for the microcontroller, as well as the computing power of the core used.Conclusions. Experimental studies show the reliability of the theoretical research presented herein. The results obtained can be used to select the optimal element base and develop software for speed controllers of electric motors of the propellers of unmanned aircraft.